A low water absorption ceramic tile prepared by using ceramic waste and a preparation method thereof
By using ceramic waste to prepare powder A and powder B, and using low-temperature eutectic technology, the problem of high firing temperature of existing low-water absorption ceramic tiles is solved, low energy consumption and low cost production is achieved, and the recycling of ceramic waste is promoted.
Patent Information
- Application Number
- CN202310676710.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-08
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-06-08
AI Technical Summary
The high firing temperature of existing low-water absorption tiles leads to large energy consumption and high production costs. At the same time, poor ceramic waste treatment, resulting in environmental pollution and waste of resources.
By using ceramic waste materials such as polished waste slag, cinder, waste glaze slag, sewage filter sludge and ceramic waste tiles, powder A and powder B are prepared, and spray granulation and low-temperature eutectic technology can reduce the firing temperature to 1070-1130℃, thereby achieving the preparation of low water absorption ceramic tiles.
It effectively reduces the firing energy consumption of low-water absorption ceramic tiles, reduces production costs, and realizes the recycling of ceramic waste, reducing environmental pollution.
Smart Images

Figure BDA0004274996250000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building ceramics, and in particular to a low-water-absorption ceramic tile prepared by using ceramic waste and a preparation method thereof. Background Art
[0002] As mineral raw materials are becoming increasingly depleted, the world's energy supply is becoming increasingly tight, and the energy crisis has begun to emerge. The rise in energy prices has led to a significant increase in production costs. All industries are doing their best to take effective measures to save energy and reduce consumption. The ceramic industry is a major energy consumer, accounting for a large proportion of economic energy consumption. Therefore, reducing energy consumption in the ceramic production process is an important long-term task for the ceramic industry.
[0003] In building ceramic technology, reducing firing energy consumption is an important link in reducing production costs and improving economic benefits; and the fundamental way to reduce the firing temperature of the green body is to achieve low-temperature firing of the green body. The firing temperature of existing low-water absorption ceramic tiles (referring to ceramic tile green bodies with a water absorption rate of ≤0.5%) is generally between 1180 and 1250°C, which not only consumes a lot of energy and minerals, but also makes the production cost of ceramic tile green bodies relatively high.
[0004] In addition, low water absorption ceramic tile products will generate a large amount of waste materials during the production process, such as coal slag, waste glaze residue, sewage filter mud and polishing waste residue. Since these ceramic waste materials will swell and bubble at high temperatures, a small amount of them mixed into the ceramic body will cause fatal defects of the product, and thus cannot be recycled in the body for a long time. Most ceramic product manufacturers use landfill to treat the above waste materials, which not only increases the treatment cost and the production cost of ceramic products, but also occupies land and pollutes the environment. There are also a small number of ceramic product manufacturers that will use one or two of the waste materials for recycling and use them in the production of ceramic tiles, but the remaining waste materials will still be landfilled, and the recycling of waste materials is very limited. Summary of the invention
[0005] The purpose of the present invention is to propose a low water absorption ceramic tile prepared from ceramic waste. The low water absorption ceramic tile is prepared by compounding a variety of ceramic wastes, which is beneficial to reducing the treatment cost of ceramic waste and the production cost of low water absorption ceramic tiles. It can also effectively reduce the energy consumption of firing low water absorption ceramic tiles to overcome the shortcomings of the prior art.
[0006] Another object of the present invention is to propose a method for preparing the above-mentioned low water absorption ceramic tiles, which has simple steps and strong operability, and can effectively treat a large amount of ceramic waste generated in the production process of low water absorption ceramic tile products, thereby realizing the recycling of waste.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] A low water absorption ceramic tile prepared from ceramic waste, comprising A powder and B powder, and the addition amount of A powder is 30-70% calculated by mass percentage;
[0009] Calculated by mass percentage, the A powder material includes 10-50% of polishing waste slag, 5-30% of coal slag, 0-20% of ironmaking waste slag, 20-40% of high-temperature potassium sand, 5-15% of bentonite I and 10-20% of A mud material;
[0010] Calculated by mass percentage, the B powder includes 1-10% of waste glaze residue, 1-10% of sewage filter mud, 2-20% of ceramic waste bricks, 10-20% of medium-temperature potassium sand, 15-25% of albite, 1-10% of magnesia clay, 1-6% of talc, 1-5% of wollastonite, 1-10% of bentonite II and 15-25% of B mud.
[0011] Preferably, in terms of mass ratio, the mixing ratio of the polishing waste residue and the coal slag is 1:(0.2-0.5).
[0012] Preferably, the Al2O3 content of the coal slag is 37-40% by mass percentage;
[0013] The melting temperature of the high-temperature potassium sand is 1130-1180°, the melting temperature of the polishing waste slag is 800-850°, and the melting temperature of the ironmaking waste slag is 1000-1150°.
[0014] Preferably, the A mud material includes any one of plaster and white mud.
[0015] Preferably, the melting temperature of the medium-temperature potash sand is 1000-1050°.
[0016] Preferably, the B mud material includes any one of black mud, gray mud and white mud.
[0017] Preferably, calculated by mass percentage, the chemical composition of the polishing waste residue includes SiO2 65-70%, Al2O3 16-20%, Fe2O3 0.9-1.3%, CaO 2.0-2.5%, MgO 1.5-2.0%, K2O 3.0-4.0%, Na2O 2.5-3.5% and loss on ignition 4.0-5.0%;
[0018] Calculated by mass percentage, the chemical composition of the coal slag includes SiO2 45-50%, Al2O3 36-40%, Fe2O3 5.0-5.5%, CaO 4.5-5.0%, MgO 0.8-1.0%, TiO2 1.0-1.5%, K2O 0.5-1.5%, Na2O 1.0-1.3% and ignition loss 1.0-2.0%.
[0019] Preferably, calculated by mass percentage, the chemical composition of the ironmaking waste slag includes SiO2 8.0-15%, Al2O3 2.0-8.0%, K2O 0-2.0%, Na2O 4.0-6.5%, CaO 2.0-5.0%, MgO 1.5-3.5%, TiO2 5.0-8.5%, Fe2O3 45-55%, V2O5 1.0-2.0%, P2O5 2.0-4.0%, Cr2O3 0.5-2.0%, MnO 4.0-8.0% and loss on ignition 0-5.0%.
[0020] Preferably, the chemical composition of the waste glaze slag includes SiO2 50-59%, Al2O3 16-25%, Fe2O3 0.3-0.6%, CaO 5.0-7.0%, MgO 4.0-5.0%, K2O 1.0-2.0%, Na2O 3.0-4.0%, ZnO 4.0-5.0% and loss on ignition 1.0-2.0% calculated by mass percentage;
[0021] Calculated by mass percentage, the chemical composition of the sewage filter press mud includes SiO2 65-67%, Al2O3 17-18%, Fe2O3 1.3-1.7%, CaO 0.9-1.3%, MgO 0.8-1.5%, K2O 3.0-4.0%, Na2O 2.5-3.5% and ignition loss 6.0-7.0%;
[0022] Calculated by mass percentage, the chemical composition of the ceramic waste bricks includes SiO2 65-70%, Al2O3 17-20%, Fe2O3 0.6-0.9%, CaO 0.7-0.9%, MgO 0.8-1.2%, K2O 3.0-4.0%, Na2O 2.0-2.5% and ignition loss 4.0-7.0%.
[0023] A method for preparing low water absorption ceramic tiles using ceramic waste, used for preparing the low water absorption ceramic tiles, comprises the following steps:
[0024] (1) adding water to the raw materials of powder A according to the proportion, ball-milling, and spray granulating to obtain powder A;
[0025] (2) adding water to the raw materials of B powder according to the proportion, ball-milling, and spray granulating to obtain B powder;
[0026] (3) Powder A and powder B are mixed in proportion, pressed, dried and fired to obtain low water absorption ceramic tiles; wherein the firing temperature of the low water absorption ceramic tiles is 1070-1130°.
[0027] The technical solution provided by the embodiments of the present application may have the following beneficial effects:
[0028] 1. Utilize coal slag with high aluminum content and high-temperature potassium sand with high melting temperature, and match polishing waste slag and ironmaking waste slag with low melting temperature, on the one hand, to increase the initial melting temperature of the formula system, and on the other hand, to make the calcium and magnesium components in the polishing waste slag and ironmaking waste slag melt with the potassium sand components in the formula system at low temperature, so that the A powder forms a formula system that can be completely sintered below 1050 degrees. In addition, since the polishing waste slag and ironmaking waste slag in the raw materials are rich in calcium, magnesium and iron components, on the basis of making full use of the fluxing effect of the above components, reduce the introduction of other low-temperature fluxes in the formula, such as sodium, titanium, barium, zinc, etc., to achieve the purpose of expanding the sintering range of A powder.
[0029] 2. By adding medium-temperature potassium sand, sodium feldspar, magnesia soil, talc, wollastonite, bentonite and mud into the formula system of B powder, calcium, magnesium, potassium, sodium and other ingredients can be introduced into the formula system to achieve the effect of low-temperature fusion of the B powder formula system.
[0030] 3. By limiting the ratio of A powder and B powder in this scheme, low water absorption tiles prepared from ceramic waste can use the existing kiln structure of low water absorption tiles. There is no need to adjust the kiln structure of existing low water absorption tiles, and low water absorption tiles can be prepared from ceramic waste, saving equipment adjustment costs. DETAILED DESCRIPTION
[0031] A low water absorption ceramic tile prepared from ceramic waste, comprising A powder and B powder, and the addition amount of A powder is 30-70% calculated by mass percentage;
[0032] Calculated by mass percentage, the A powder material includes 10-50% of polishing waste slag, 5-30% of coal slag, 0-20% of ironmaking waste slag, 20-40% of high-temperature potassium sand, 5-15% of bentonite I and 10-20% of A mud material;
[0033] Calculated by mass percentage, the B powder includes 1-10% of waste glaze residue, 1-10% of sewage filter mud, 2-20% of ceramic waste bricks, 10-20% of medium-temperature potassium sand, 15-25% of albite, 1-10% of magnesia clay, 1-6% of talc, 1-5% of wollastonite, 1-10% of bentonite II and 15-25% of B mud.
[0034] In order to consume the large amount of waste generated in the production process of low water absorption ceramic tiles and reduce the treatment cost of ceramic waste, the present technical scheme proposes a low water absorption ceramic tile prepared from ceramic waste, which mainly utilizes five types of ceramic waste, namely polishing waste residue, coal slag, waste glaze residue, sewage filter mud and ceramic waste bricks, as the main production raw materials, and cooperates with the use of iron smelting waste residue in the iron smelting industry to effectively prepare ceramic tiles with low water absorption, realize the recycling of waste in the production process of low water absorption ceramic tiles, and at the same time reduce the firing energy consumption in the preparation process of the above-mentioned ceramic tiles, thereby overcoming the shortcomings of the prior art.
[0035] It should be noted that polishing slag is a common waste material in the field of building ceramics. It is mainly produced during the grinding and polishing of ceramic tiles, and its components are mainly silicon carbide, magnesium oxide, magnesium chloride and brick chips in the grinding block.
[0036] Cinder is a solid waste produced during the firing process of ceramic tiles. It is produced in large quantities. After burning 1 ton of coal, an average of about 0.35 tons of ash is produced. Cinder contains a large amount of SiO2, Al2O3, Fe2O3 and CaO, as well as a small amount of residual calorific value. Therefore, studying the application of recycled ash in the formulation of ceramic green bodies not only reduces the consumption of traditional raw materials, but also can make better use of waste ash and realize the resource utilization of waste, which is beneficial to both cost saving and environmental protection.
[0037] In addition, during the production of ceramic tiles, a certain amount of waste glaze water will be generated during the glaze making in the ball glaze workshop, ball washing and cleaning equipment, and glaze dripping during the glaze line production process. After precipitation and squeezing, the waste glaze water will produce waste glaze residue. Although the waste glaze residue has the properties of glaze, it is mixed with other ingredients and is difficult to be used in the production of high-quality ceramic tile products in the form of glaze. Moreover, the waste glaze residue has a low firing temperature, a large amount of low-temperature melting raw materials, a high degree of high-temperature melting, and a low high-temperature viscosity. If it is directly applied to the blank, it is easy to increase the amount of liquid phase produced during the firing of the blank, resulting in the brick shape and wave pattern of the kiln bricks being difficult to control.
[0038] Sewage filter press mud is the remaining mud after the base material and surface material of the ceramic factory are washed in the slurry pool and spray tower, and then treated in the sedimentation tank for secondary treatment, and then squeezed out the water by the filter press. In the existing technology, it is generally discarded.
[0039] There are generally two types of ceramic waste bricks. One is the unqualified products that cannot be recycled and are produced and discovered during the firing process, processing process and product inspection process. The other is the scraps obtained by trimming the ceramic tiles during the actual production process of the ceramic tiles to ensure that the straightness and edge straightness of the finished ceramic tiles are within an appropriate range.
[0040] Specifically, the low water absorption ceramic tiles prepared by using ceramic waste proposed in this scheme include A powder and B powder.
[0041] First, according to the mass percentage, the A powder in this scheme includes 10-50% polishing waste slag, 5-30% coal slag, 0-20% ironmaking waste slag, 20-40% high-temperature potassium sand, 5-15% bentonite I and 10-20% A mud. Since the ceramic waste in the A powder is easy to oxidize and foam at high temperature, in order to prevent the formula system from melting before the gas is completely discharged, resulting in the pores being closed and unable to be discharged smoothly and / or violently discharged, causing pinholes, bubbles and even bulges on the surface of the green body after firing, this scheme uses coal slag with a high aluminum content and high-temperature potassium sand with a high melting temperature, and matches polishing waste slag and ironmaking waste slag with a low melting temperature, on the one hand, to increase the initial melting temperature of the formula system, and on the other hand, to make the calcium and magnesium components in the polishing waste slag and ironmaking waste slag melt at low temperature with the potassium sand component in the formula system, so that the A powder forms a formula system that is completely sintered below 1050 degrees. In addition, since the polishing waste slag and ironmaking waste slag in the raw materials are rich in calcium, magnesium and iron, on the basis of fully utilizing the fluxing effect of the above components, the introduction of other low-temperature fluxes in the formula, such as sodium, titanium, barium, zinc, etc., is reduced to achieve the purpose of expanding the sintering range of A powder.
[0042] Secondly, calculated by mass percentage, the B powder in this scheme includes 1-10% of waste glaze residue, 1-10% of sewage filter mud, 2-20% of ceramic waste bricks, 10-20% of medium-temperature potash sand, 15-25% of sodium feldspar, 1-10% of magnesia soil, 1-6% of talc, 1-5% of wollastonite, 1-10% of bentonite II and 15-25% of B mud. Since the ceramic waste in the B powder has the common point of not foaming at high temperature, and the loss on ignition of the waste glaze residue is low, by adding medium-temperature potash sand, sodium feldspar, magnesium soil, talc, wollastonite, bentonite and mud to the formula system of the B powder, calcium, magnesium, potassium, sodium and other ingredients can be introduced into the formula system to achieve the effect of low-temperature fusion of the B powder formula system. It should also be noted that the chemical composition of bentonite I in the A powder and bentonite II in the B powder in this scheme can be the same or different, and I and II are only used as distinguishing marks.
[0043] Finally, the A powder and B powder that can both achieve the low-temperature eutectic effect are mixed in proportion to form ceramic tiles. Since the overall temperature of the green body formula becomes lower after low-temperature eutectic, it is beneficial to reduce the kiln temperature. After the kiln temperature is reduced, the kiln exhaust can be increased, which is beneficial to oxidation and energy saving. In addition, due to different kiln structures, the oxidation capacity they can provide is different. Through the ratio limit of A powder and B powder in this scheme, the low water absorption ceramic tiles prepared using ceramic waste can use the existing kiln structure of low water absorption ceramic tiles. There is no need to adjust the kiln structure of the existing low water absorption ceramic tiles. Ceramic waste can be used to prepare low water absorption ceramic tiles, saving equipment adjustment costs.
[0044] This scheme is a low water absorption ceramic tile made of ceramic waste, which uses ceramic waste as the main raw material and also adds iron smelting waste slag from the iron smelting industry. The raw materials are easy to obtain and the production cost is low. After resource utilization, a large amount of land can be saved and environmental protection can be achieved. Furthermore, by adjusting the formula, the ceramic tile can reduce the firing energy consumption in the production process while meeting the relevant performance requirements.
[0045] To further illustrate, in terms of mass ratio, the mixing ratio of the polishing waste residue and the coal slag is 1:(0.2-0.5).
[0046] Since the silicon carbide component in the polishing waste slag will oxidize at high temperature, generate silicon dioxide and release carbon dioxide, thereby generating a large number of bubbles. In a preferred embodiment of the present technical solution, by setting the mass ratio of the polishing waste slag to the coal slag to preferably 1: (0.2-0.5), the strong reducing property of the high temperature solidified carbon element remaining in the coal slag is utilized to form a certain reducing atmosphere in the internal micro space of the spray powder particles, which plays a role in preventing the silicon carbide component in the polishing waste slag from violently oxidizing at high temperature, so that the product is completely sintered at low temperature, and the surface of the green body does not bubble, while the compactness of the green body structure is not destroyed.
[0047] Further, the Al2O3 content of the coal slag is 37-40% calculated by mass percentage;
[0048] The melting temperature of the high-temperature potassium sand is 1130-1180°, the melting temperature of the polishing waste slag is 800-850°, and the melting temperature of the ironmaking waste slag is 1000-1150°.
[0049] Since the ceramic waste in the A powder is easily oxidized and foamed at high temperatures, in order to ensure sufficient discharge of gas, this scheme further optimizes the melting temperature of the ceramic waste in the A powder and the melting temperature of the high-temperature potassium sand matched therewith, and introduces potassium sand with a higher melting temperature to increase the initial melting temperature of the A powder eutectic, increase the oxidation time, and discharge gas.
[0050] To further explain, the A mud material includes any one of plaster and white mud.
[0051] To further illustrate, the melting temperature of the medium-temperature potash sand is 1000-1050°.
[0052] In another preferred embodiment of the present technical solution, in order to make the formula systems of powder A and powder B match each other, the melting temperature of the medium-temperature potash sand is preferably set to 1000-1050°.
[0053] To further explain, the B mud material includes any one of black mud, gray mud and white mud.
[0054] Further, the chemical composition of the polishing waste residue includes SiO2 65-70%, Al2O3 16-20%, Fe2O3 0.9-1.3%, CaO 2.0-2.5%, MgO 1.5-2.0%, K2O 3.0-4.0%, Na2O 2.5-3.5% and loss on ignition 4.0-5.0% calculated by mass percentage;
[0055] Calculated by mass percentage, the chemical composition of the coal slag includes SiO2 45-50%, Al2O3 36-40%, Fe2O3 5.0-5.5%, CaO 4.5-5.0%, MgO 0.8-1.0%, TiO2 1.0-1.5%, K2O 0.5-1.5%, Na2O 1.0-1.3% and ignition loss 1.0-2.0%.
[0056] To further illustrate, calculated by mass percentage, the chemical composition of the ironmaking waste slag includes SiO2 8.0-15%, Al2O3 2.0-8.0%, K2O 0-2.0%, Na2O 4.0-6.5%, CaO 2.0-5.0%, MgO 1.5-3.5%, TiO2 5.0-8.5%, Fe2O3 45-55%, V2O5 1.0-2.0%, P2O5 2.0-4.0%, Cr2O3 0.5-2.0%, MnO 4.0-8.0% and loss on ignition 0-5.0%.
[0057] Further, the chemical composition of the waste glaze residue includes SiO250-59%, Al2O316-25%, Fe2O30.3-0.6%, CaO 5.0-7.0%, MgO 4.0-5.0%, K2O 1.0-2.0%, Na2O3.0-4.0%, ZnO 4.0-5.0% and loss on ignition 1.0-2.0% according to mass percentage;
[0058] Calculated by mass percentage, the chemical composition of the sewage filter press mud includes SiO2 65-67%, Al2O3 17-18%, Fe2O3 1.3-1.7%, CaO 0.9-1.3%, MgO 0.8-1.5%, K2O 3.0-4.0%, Na2O 2.5-3.5% and ignition loss 6.0-7.0%;
[0059] Calculated by mass percentage, the chemical composition of the ceramic waste bricks includes SiO2 65-70%, Al2O3 17-20%, Fe2O3 0.6-0.9%, CaO 0.7-0.9%, MgO 0.8-1.2%, K2O 3.0-4.0%, Na2O 2.0-2.5% and ignition loss 4.0-7.0%.
[0060] A method for preparing low water absorption ceramic tiles using ceramic waste, used for preparing the low water absorption ceramic tiles, comprises the following steps:
[0061] (1) adding water to the raw materials of powder A according to the proportion, ball-milling, and spray granulating to obtain powder A;
[0062] (2) adding water to the raw materials of B powder according to the proportion, ball-milling, and spray granulating to obtain B powder;
[0063] (3) Powder A and powder B are mixed in proportion, pressed, dried and fired to obtain low water absorption ceramic tiles; wherein the firing temperature of the low water absorption ceramic tiles is 1070-1130°.
[0064] This proposal also proposes a method for preparing the above-mentioned low water absorption ceramic tile, which has simple steps and strong operability, and can effectively treat a large amount of ceramic waste generated during the production process of low water absorption ceramic tile products, thereby realizing the recycling of waste materials. In addition, the firing temperature of the low water absorption ceramic tile reaches 1070-1130°, which can effectively reduce the energy consumption during the ceramic tile production process.
[0065] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0066] Example 1
[0067] (1) adding water to the raw materials of powder A according to the proportion, ball-milling, and spray granulation to obtain powder A; wherein, calculated by weight percentage, the powder A includes 10% of polishing waste slag with a melting temperature of 800-850°, 30% of coal slag with an Al2O3 content of 37-40wt%, 10% of ironmaking waste slag with a melting temperature of 1000-1150°, 30% of high-temperature potassium sand with a melting temperature of 1130-1180°, 5% of bentonite I, and 15% of plaster;
[0068] (2) adding water to the raw materials of B powder according to the proportion, ball-milling, and spray granulating to obtain B powder; wherein, calculated by mass percentage, the B powder includes 5% of waste glaze residue, 10% of sewage filter mud, 5% of ceramic waste bricks, 10% of medium-temperature potash sand with a melting temperature of 1000-1050°, 25% of albite, 5% of magnesia clay, 8% of talc, 3% of wollastonite, 5% of bentonite II and 24% of black mud;
[0069] (3) According to the mass percentage, 30% of A powder and 70% of B powder are mixed, pressed, dried and fired at a temperature of 1070-1130° to obtain low water absorption ceramic tiles.
[0070] Example 2
[0071] (1) adding water to the raw materials of powder A according to the proportion, ball-milling, and spray granulation to obtain powder A; wherein, calculated by weight percentage, the powder A includes 20% of polishing waste slag with a melting temperature of 800-850°, 10% of coal slag with an Al2O3 content of 37-40wt%, 20% of ironmaking waste slag with a melting temperature of 1000-1150°, 20% of high-temperature potassium sand with a melting temperature of 1130-1180°, 10% of bentonite I, and 20% of white mud;
[0072] (2) adding water to the raw materials of B powder according to the proportion, ball-milling, and spray granulating to obtain B powder; wherein, calculated by mass percentage, the B powder includes 10% of waste glaze residue, 5% of sewage filter mud, 2% of ceramic waste bricks, 20% of medium-temperature potassium sand with a melting temperature of 1000-1050°, 25% of albite, 10% of magnesia clay, 5% of talc, 5% of wollastonite, 3% of bentonite II and 15% of plaster;
[0073] (3) According to the mass percentage, 50% of A powder and 50% of B powder are mixed, pressed, dried and fired at a temperature of 1070-1130° to obtain low water absorption ceramic tiles.
[0074] Example 3
[0075] (1) adding water to the raw materials of powder A according to the proportion, ball-milling, and spray granulation to obtain powder A; wherein, calculated by weight percentage, the powder A includes 50% of polishing waste slag with a melting temperature of 800-850°, 5% of coal slag with an Al2O3 content of 37-40wt%, 20% of high-temperature potassium sand with a melting temperature of 1130-1180°, 15% of bentonite I, and 10% of plaster;
[0076] (2) adding water to the raw materials of B powder according to the proportion, ball-milling, and spray granulating to obtain B powder; wherein, calculated by mass percentage, the B powder includes 1% of waste glaze residue, 1% of sewage filter mud, 20% of ceramic waste bricks, 15% of medium-temperature potassium sand with a melting temperature of 1000-1050°, 15% of albite, 2% of magnesia clay, 6% of talc, 5% of wollastonite, 10% of bentonite II and 25% of white mud;
[0077] (3) According to the mass percentage, 70% of A powder and 30% of B powder are mixed, pressed, dried and fired at a temperature of 1070-1130° to obtain low water absorption ceramic tiles.
[0078] Performance Testing
[0079] According to the preparation method in Examples 1-3, low water absorption ceramic tiles were prepared, and the process parameters not mentioned in the steps of Examples 1-3 were ensured to be consistent. The morphology and surface effect of the green body were observed. The low water absorption ceramic tiles in the above examples were subjected to conventional water absorption and rupture modulus tests in the ceramic field. The performance test results are shown in Table 1 below:
[0080] Table 1 Performance test results of different low water absorption tiles
[0081]
[0082] From the above performance test results, it can be seen that the low water absorption ceramic tile blank prepared by the preparation method of this scheme has a smooth surface without bubbles and no blackening in the center of the blank. It can be fired at a temperature of 1070-1130°. The water absorption of the prepared ceramic tile is ≤0.5%, and the modulus of rupture is ≥38MPa, which meets the production standards of low water absorption ceramic tiles.
[0083] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.
Claims
1. A low water absorption ceramic tile prepared from ceramic waste, characterized in that: The raw materials are composed of A powder and B powder, and the addition amount of A powder is 30-70% by weight; the water absorption rate of the low water absorption rate is ≤0.5%; Calculated by mass percentage, the raw materials of the A powder are composed of 10-50% polishing waste slag, 5-30% coal slag, 0-20% ironmaking waste slag, 20-40% high-temperature potassium sand, 5-15% bentonite I and 10-20% A mud; Calculated by mass percentage, the raw materials of the B powder are composed of 1-10% waste glaze residue, 1-10% sewage filter mud, 2-20% ceramic waste bricks, 10-20% medium-temperature potassium sand, 15-25% albite, 1-10% magnesia clay, 1-6% talc, 1-5% wollastonite, 1-10% bentonite II and 15-25% B mud; According to the mass ratio, the mixing ratio of the polishing waste slag and the coal slag is 1: (0.2-0.5), and according to the mass percentage, the Al2O3 content of the coal slag is 37-40%; The melting temperature of the high-temperature potash sand is 1130-1180°C, and the melting temperature of the medium-temperature potash sand is 1000-1050°C; The A mud material is any one of plaster and white mud, and the B mud material is any one of black mud, plaster and white mud.
2. The low water absorption ceramic tile prepared from ceramic waste according to claim 1, characterized in that: The melting temperature of the polishing waste slag is 800-850°C, and the melting temperature of the ironmaking waste slag is 1000-1150°C.
3. The low water absorption ceramic tile prepared from ceramic waste according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the polishing waste residue includes SiO2 65-70%, Al2O3 16-20%, Fe2O3 0.9-1.3%, CaO 2.0-2.5%, MgO 1.5-2.0%, K2O 3.0-4.0%, Na2O 2.5-3.5% and ignition loss 4.0-5.0%.
4. The low water absorption ceramic tile prepared from ceramic waste according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the ironmaking waste slag includes SiO2 8.0-15%, Al2O3 2.0-8.0%, K2O 0-2.0%, Na2O 4.0-6.5%, CaO 2.0-5.0%, MgO 1.5-3.5%, TiO2 5.0-8.5%, Fe2O3 45-55%, V2O5 1.0-2.0%, P2O5 2.0-4.0%, Cr2O3 0.5-2.0%, MnO 4.0-8.0% and loss on ignition 0-5.0%.
5. The low water absorption ceramic tile prepared from ceramic waste according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the waste glaze residue includes SiO2 50-59%, Al2O3 16-25%, Fe2O3 0.3-0.6%, CaO 5.0-7.0%, MgO 4.0-5.0%, K2O 1.0-2.0%, Na2O 3.0-4.0%, ZnO 4.0-5.0% and loss on ignition 1.0-2.0%; Calculated by mass percentage, the chemical composition of the sewage filter press mud includes SiO2 65-67%, Al2O3 17-18%, Fe2O3 1.3-1.7%, CaO 0.9-1.3%, MgO 0.8-1.5%, K2O 3.0-4.0%, Na2O 2.5-3.5% and ignition loss 6.0-7.0%; Calculated by mass percentage, the chemical composition of the ceramic waste bricks includes SiO2 65-70%, Al2O3 17-20%, Fe2O3 0.6-0.9%, CaO 0.7-0.9%, MgO 0.8-1.2%, K2O 3.0-4.0%, Na2O 2.0-2.5% and ignition loss 4.0-7.0%.
6. A method for preparing low water absorption ceramic tiles using ceramic waste, characterized in that: The method for preparing the low water absorption ceramic tile according to any one of claims 1 to 5 comprises the following steps: (1) Add water to the raw materials of powder A according to the proportion, ball-mill and spray granulate to obtain powder A; (2) Add water to the raw materials of B powder according to the proportion, ball mill and spray granulate to obtain B powder; (3) Mixing powder A and powder B in proportion, pressing, drying and firing to obtain low water absorption ceramic tiles; wherein the firing temperature of the low water absorption ceramic tiles is 1070-1130°C.
Citation Information
Patent Citations
Method for producing foamed red mud decoration ceramic tile by using roller hearth kiln
CN104844254A
Method for treating solid waste slags in production process of ceramic tiles
CN109180148A